Analisa Bisnis Ekonomi Kreatif Sub Sektor Fashion Untuk Meningkatkat Kepatuhan Wajib Pajak (Studi Kasus Pada Pelaku Ekonomi Kreatif di Kota Malang) - Wardatul Jannah; Jeni Susyanti; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThe purpose of this study was to analyze creative economic entrepreneurs of the fashion sub-sector to improve taxpayer compliance. The population is 60 fashion sub-sector creative economic entrepreneurs in Malang City. The sampling technique uses purposive sampling methods. Data collection was carried out using primary data through interviews, questionnaire and obserrvation. The data testing techniques used in this study include instrument data test, normality test, and simple linear regression analysis. By looking at the result of the analysis and discussion of the data, this research obtain conclusions that can be drawn from the research on the analyze creative economic entrepreneurs in the fashion sub-sector in order to meet taxpayer compliance in Malang city is still not high enough, because based on the results of the analysis show that the fashion sub-sector creative economic business significantly on negative affects taxpayer compliance with a t-count value of-0,518 and a significance value of 0,606. The significance of the negative coefficient means that there is a negative relationship between variable X and Y, the more the creative economy of the fashion sector (X) increases, the lower the taxpayer compliance (Y). Keywords: creative economic, fashion, taxpayer compliance.